2022
DOI: 10.3389/fpls.2022.1022369
|View full text |Cite
|
Sign up to set email alerts
|

Insights into transcription factors controlling strawberry fruit development and ripening

Abstract: Fruit ripening is a highly regulated and complex process involving a series of physiological and biochemical changes aiming to maximize fruit organoleptic traits to attract herbivores, maximizing therefore seed dispersal. Furthermore, this process is of key importance for fruit quality and therefore consumer acceptance. In fleshy fruits, ripening involves an alteration in color, in the content of sugars, organic acids and secondary metabolites, such as volatile compounds, which influence flavor and aroma, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 115 publications
0
7
0
Order By: Relevance
“…Transcription factor genes identified by RNAi experiments also resulted in white fruits such as ripening induced factor ( FaRIF ) ( Martín-Pizarro et al , 2021 ) or related to ABI3/viviparous 1 ( FaRAV ) ( Zhang et al , 2020 ). However, a more detailed review of the TFs controlling strawberry ripening was recently published by Sánchez-Gómez et al (2022) , and we refer readers to this for further details.…”
Section: Berries and Receptacle Fruitsmentioning
confidence: 99%
“…Transcription factor genes identified by RNAi experiments also resulted in white fruits such as ripening induced factor ( FaRIF ) ( Martín-Pizarro et al , 2021 ) or related to ABI3/viviparous 1 ( FaRAV ) ( Zhang et al , 2020 ). However, a more detailed review of the TFs controlling strawberry ripening was recently published by Sánchez-Gómez et al (2022) , and we refer readers to this for further details.…”
Section: Berries and Receptacle Fruitsmentioning
confidence: 99%
“…Ripening of fleshy fruits is a highly complex process that involves dramatic changes in sugar content, fruit color, fruit texture, flavor, and aroma [3,4]. In recent years, the mechanisms of fruit ripening have been studied extensively at the transcriptional level, and many transcription factors as well as 5-methylcytosine (5mC) DNA methylation at various gene loci have been identified and proven to be responsible for transcriptional regulation 2 of 13 of gene expression during the ripening process [5,6]. In addition, a series of studies have demonstrated that posttranscriptional control also plays vital roles in fruit ripening such as AS, APA, mRNA N6-methyladenosine RNA modification methylation and noncoding RNAs [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been demonstrated that the auxin and/or gibberellic acid (GA) inhibit strawberry fruit ripening [ 6 , 7 ]. To date, a large number of TFs belonging to the B-box, bHLH, MYB, MADS-box, and bZIP TF families, have been identified to participate in the strawberry fruit development and ripening process by crosstalk with phytohormones or regulation of related genes [ 8 ]. In addition, DNA hypomethylation [ 9 ] and N 6 -methyladenosine RNA modification [ 10 ] also regulate strawberry fruit ripening.…”
Section: Introductionmentioning
confidence: 99%